The Influence of Job Description and Job Satisfaction on Employee Productivity in the Blower Motor Assy Production Department - Wulandari, Wulandari (Lentera Ilmu Nusantara, 2023)
This research aims to explore and analyze the influence of job descriptions and job satisfaction on employee productivity in the blower motor assembly production department of PT. Denso Manufacturing Indonesia. Data collection was carried out by distributing questionnaires to the total population and sample of 42 respondents, using a quantitative descriptive approach. The data analysis used is the R square Algorithm Test analysis, and Path Coefficient Boostrapping. The results of this research show that the job description variable has a significant positive effect on employee productivity, while job satisfaction has a positive but not significant effect on employee productivity. Therefore, the test results from this research state that there is the same positive influence but has a different significant level between the job description and job satisfaction on work productivity in the blower motor assembly production department of PT. Denso Manufacturing Indonesia.